The Swedish Red List 2020 - SLU Swedish Species Information Centre (Swedish University of Agricultural Sciences, 2020)
The Swedish Red List is produced by the Swedish Species Information Centre at the Swedish University of Agricultural Sciences (SLU Artdatabanken). The Swedish Red List 2020, published on April 22 2020, is the fifth Swedish Red List based on the IUCN Red List Criteria.

The Swedish Red List is a compilation of the extinction risk of individual species and provides an overview of the status of Swedish species. Experts assess a sample of all species for which knowledge is considered sufficient. Assessments are based on criteria developed by the International Union for Conservation of Nature (IUCN), which include estimates of population size, abundance, distribution and trends, and include past, present and future changes, resulting in the species being placed in a particular category.

Further reading, species-specific information and results are available at www.artdatabanken.se/rodlistning.
Keywords: Checklist; Checklist; conservation; biodiversity; IUCN; Red List; red-listed species; CHECKLIST; Biological Sciences; Biologi